Multilocus sequence typing (MLST) de isolados de complexo Klebsiella pneumoniae humanos e animais - Sousa, Alessandra Tammy Hayakawa Ito de (2022)
One of the biggest public health concerns are multidrug-resistant microorganisms (MDR) and Klebsiella spp. has a great importance in human and veterinary medicine, causing different types of infections. With close contact between humans and domestic and wild animals, there is a risk of zoonotic diseases and the spread of multidrug-resistant superbugs. Aiming at the One health concept, animals, humans and the environment can act as reservoirs and disseminators of MDR superbugs. The objective of this work was to trace the degree of similarity between the isolates of the Klebsiella spp. detected in humans, domestic and wild animals, in addition to verifying the spread of resistant clones within the state of Mato Grosso and comparing with epidemiological data from different regions of Brazil and the world. The isolates from different lesion sites were identified and confirmed by the sequencing of the 16S rRNA gene as belonging to the K. pneumoniae complex and the antimicrobial susceptibility test was performed by the disk diffusion method in animals and in humans by the Inhibitory Concentration method. Minimum (MIC) performed in Bact / Alert 3D and Vitek2 systems. The extracted isolates were submitted to the Multi Locus Sequence Typing (MLST) technique as described by the Pasteur Institute. A total of 85% (62/73) of all isolates in this study were found to be multidrug resistant (MDR). In isolates from domestic and wild animals, high rates of resistance to amoxicillin 97% (56/58), ampicillin 93% (54/58), sulfonamides 93% (54/58) and nitrofurantoin 91% (53/58) were observed. Lower rates were found in amikacin 17% (10/58), meropenem 7% (4/58) and imipenem 3% (2/58) with 93% (54/58) of isolates from animals considered MDR. Human isolates showed high resistance to beta lactams, mainly to ampicillin 100% (15/15) and lower resistance to amikacin 13% (02/15) and colistin 33% (05/15), with 53% (08/15) of these, considered MDR. 60 Sequence type (ST) were found and of these, 20 were considered new ST, as there was detection of new alleles and there was no predominance of STs. Due to the few data on infection in wild and domestic animals in the state of Mato Grosso, Brazil, which has 3 biomes such as the Pantanal, Amazon and Cerrado, and considering the importance of Klebsiella spp. at One Health, knowledge of the population structure of the K. pneumoniae complex is needed to determine the relationship between MDR organisms as well as the source of infection during outbreaks providing data for greater public health control.